ENCAPSULATION OF ANTITUBERCULAR DRUGS BY BIOPOLYMERS AND POLYELECTROLYTE MULTILAYERS - B. H. Mussabayeva; K. B. Murzagulova; M. E. Kim; V. A. Izumrudov; Z. Zh. Aripzhanova (Фармация и фармакология (Пятигорск), 2017)
The problem of drug-resistant tuberculosis treatment is complex and urgent: the standardof treatment includes the oral administration of six names of antibiotics, i.e. up totwenty tablets a day by the patient. This causes severe side effects, including those appeareddue to the formation of toxic products of drug interactions in the body. Therefore, itis important that some drugs dissolve in a stomach, and others – in the intestine, which willlead to increased bioavailability, reduced dosage and toxicity. The development of targeteddelivery systems for drugs with controlled release, targeted delivery and minimization ofside effects are of interest. One of the promising methods is polyelectrolytic multilayersand the technology of creating such layers by a step-by-step adsorption of heterogeneouslycharged polyelectrolytes.The aim of this article is the microencapsulation of anti-tuberculousdrugs into biopolymers coated with polyelectrolytic multilayers, and the solubilitystudy of microcapsules at pH values simulating various parts of the gastrointestinal tract.Materials and methods. Drugs as isoniazide, pyrazinamide, moxifloxacin, and biopolymers:gellan, pectin and sodium alginate, chitosan and dextran sulfate, as well as EudragitS are used to prepare microcapsules. The obtained microcapsules are studied by a methodof scanning electron microscopy. Quantitative determination of the effectiveness of the inclusionof drugs in microcapsules was carried out using pharmacopoeial methods.Results and discussion. The inclusion efficiency rises with an increase of biopolymer concentration. The inclusion efficiency increases in the row isoniazide <pyrazinamide <moxifloxacin. The possibility of microencapsulation of anti-tuberculosis drugs of pyrazinamide, isoniazide and moxifloxacin by means of coating with polyelectrolytic multilayers is shown.At pH = 7.4, the degree of release of the drugs from microcapsules without applied multilayersfor 12 hours was more than 80%, i.e. the prolongation was 12 hours. In the caseof microcapsules coated with polyelectrolytic multilayers: for 12 hours – 55/50%, for 18hours – more than 87/80%.Conclusion. The possibility of preparation of microcapsules of anti-tuberculosis drugs using biopolymers coated with polyelectrolytic layers, having a prolonged action is up to 18 hours, i1.5 times greater than that without coating.